Real-world clinical outcomes and cost estimates of metastatic castration-resistant prostate cancer treatment: does sequencing of taxanes and androgen receptor-targeted agents matter?. (7th February 2023) - Pereira-Salgado, Amanda; Anton, Angelyn; Franchini, Fanny; Mahar, Robert K.; Kwan, Edmond M.; Wong, Shirley; Shapiro, Julia; Weickhardt, Andrew; Azad, Arun A.; Spain, Lavinia; Gunjur, Ashray; Torres, Javier; et al.
ABSTRACT: Introduction: Health economic outcomes of real-world treatment sequencing of androgen receptor-targeted agents (ARTA) and docetaxel (DOC) remain unclear. Material and Methods: Data from the electronic Castration-resistant Prostate cancer Australian Database (ePAD) were analyzed including median overall survival (mOS) and median time-to-treatment failure (mTTF). Mean total costs (mTC) and incremental cost-effectiveness ratios (ICER) of treatment sequences were estimated using the average sample method and Zhao and Tian estimator. Results: Of 752 men, 441 received ARTA, 194 DOC, and 175 both sequentially. Of participants treated with both, first-line DOC followed by ARTA was the more common sequence (n = 125, 71%). mOS for first-line ARTA was 8.38 years (95% CI: 3.48, not-estimated) vs. 3.29 years (95% CI: 2.92, 4.02) for DOC. mTTF was 15.7 months (95% CI: 14.2, 23.7) for the ARTA-DOC sequence and 18.2 months (95% CI: 16.2, 23.2) for DOC-ARTA. In first-line, ARTA cost an additional 13, 244 per mTTF month compared to DOC. In second-line, ARTA cost 6726 per mTTF month. The DOC-ARTA sequence saved 2139 per mTTF compared to ARTA-DOC, though not statistically significant. Conclusion: ICERs show ARTA had improved clinical benefit compared to DOC but at higher cost. There were no significant cost differences between combined sequences.